The Effect of Organizational Climate on Organizational Commitment in 2022: Case Study -Gaza Electricity Distribution Corporation - Wasim M. H. Swidan; Ali Nasser Al-Tahitah; Kalsom Ali (Arab Institute of Science and Research P, 2024)
Non-Indexed Publication